Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd004453.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal surgical incisions for caesarean section

Abstract: The Joel-Cohen incision has advantages compared to the Pfannenstiel incision. These are less fever, pain and analgesic requirements; less blood loss; shorter duration of surgery and hospital stay. These advantages for the mother could be extrapolated to savings for the health system. However, these trials do not provide information on severe or long-term morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Likewise, the choice between a Pfannenstiel and a Joel-Cohen incision in obese patients has not been the subject of investigation. There is some evidence from RCTs to suggest that the Joel-Cohen incision has advantages over the Pfannenstiel incision in the general population, with a reduction in post-operative febrile morbidity (RR 0.35, 95% CI 0.14e0.87), in delivery and operating time, as well as estimated blood loss and post-operative analgesic requirements [32]. In obese patients, however, it is generally easy with Pfannenstiel incisions to dissect the subcutaneous tissue upwards and open the rectus sheath above the pyramidalis muscles, as would occur in the Joel-Cohen incision.…”
Section: Vertical or Transverse Skin Incisionmentioning
confidence: 99%
“…Likewise, the choice between a Pfannenstiel and a Joel-Cohen incision in obese patients has not been the subject of investigation. There is some evidence from RCTs to suggest that the Joel-Cohen incision has advantages over the Pfannenstiel incision in the general population, with a reduction in post-operative febrile morbidity (RR 0.35, 95% CI 0.14e0.87), in delivery and operating time, as well as estimated blood loss and post-operative analgesic requirements [32]. In obese patients, however, it is generally easy with Pfannenstiel incisions to dissect the subcutaneous tissue upwards and open the rectus sheath above the pyramidalis muscles, as would occur in the Joel-Cohen incision.…”
Section: Vertical or Transverse Skin Incisionmentioning
confidence: 99%
“…In current practice, most women undergo repeat CD through a transverse skin incision, such as the Pfannenstiel or the Joel-Cohen, which provides better cosmetic results and carries a lower risk of incisional hernia [8]. Vertical skin incisions typically have been reserved for emergent situations necessitating expeditious delivery, or in settings when it is thought that greater exposure may be necessary (e.g., planning for cesarean hysterectomy) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vertical skin incisions typically have been reserved for emergent situations necessitating expeditious delivery, or in settings when it is thought that greater exposure may be necessary (e.g., planning for cesarean hysterectomy) [8]. It is possible, however, that more routine use of vertical skin incisions may provide advantage for women who have had multiple prior CDs by enabling dense adhesions in the lower abdomen to be avoided more readily, by reducing blood loss, and by allowing greater ease for cephalad extension of the skin incision if more space is required for uterine and fetal access.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different operational techniques have been defined to reduce the risk of peri-and postoperative morbidity [1]. Randomized, controlled studies have revealed discordant results regarding the optimal surgical technique [2][3][4][5][6]. The uterine repair site has been a major concern when evaluating surgical techniques.…”
Section: Introductionmentioning
confidence: 99%